Usage of unicompartmental knee arthroplasty - Murray, D; Parkinson, R (British Editorial Society of Bone and Joint Surgery, 2018)
Unicompartmental knee arthroplasty (UKA) has numerous advantages over total knee arthroplasty (TKA) and one disadvantage, the higher revision rate. The best way to minimize the revision rate is for surgeons to use UKA for at least 20% of their knee arthroplasties. To achieve this, they need to learn and apply the appropriate indications and techniques. This would decrease the revision rate and increase the number of UKAs which were implanted, which would save money and patients would benefit from improved outcomes over their lifetime.